Simulating the Computer Science Closed Laboratory in an Asynchronous Learning Network - Margush, Timothy (International Review of Research in Open and Distributed Learning, 2002)
The quiz tool that is part of the WebCT package is used to provide an asynchronous simulation of a (synchronous) closed laboratory experience to beginner computer science students. The technique suggested in this paper and which may be applied to other disciplines, offers students a guided path through an exploratory, discovery based learning experience.